Strategi Pengembangan Produksi Garam di Wini – Perbatasan Timor Leste: (Salt Production Development Strategy in Wini –Timor Leste Border) - Kamilaus Konstanse Oki; Ismi Andari; Adrianus Abani (e-Journal Ekonomi Bisnis dan Akuntansi, 2022)
Salt production in Wini on the border of Timor Leste is quite prospective because of the carrying capacity of marine resources and air temperature as well as the large domestic and foreign markets. The salt production area on the border of Timor Leste is 1,000 hectares which is located in the North Central Timor district and is the largest on the island of Timor. The production process still uses the traditional approach and other obstacles such as lack of working capital, not yet having a legal production permit. As a result, it is not feasible to process foreign exports. SWOT analysis is a solution to solve problems and find the best way to develop salt production in border areas. The purpose of the SWOT analysis is to analyze the important aspects of the strengths, weaknesses, opportunities and threats of salt production in the border region. The sample in this study were salt farmers and other related elements. The results showed that a development strategy was needed by utilizing internal strengths to take advantage of external opportunities to increase salt production capacity.